TI_GERICHTE 90.2014.32 vom 27. März 2015 , Ricorso contro un marciapiede e obbligo d'inserimento delle linee d'arretramento - TI Tribunale d'appello (2015)
Ricorso contro un marciapiede e obbligo d'inserimento delle linee d'arretramento